Model Problem Based Learning untuk meningkatkan motivasi berprestasi dan inovasi siswa pada pelajaran PAI - Sukriyatun, Gunarti; Mujahidin, Endin (Ta'dibuna: Jurnal Pendidikan Islam, 2022)
This research aims to determine current achievement motivation and innovation students in Islamic religious education students for junior high school in Bogor City. develop PBL to improve students for junior hight school Bogor City. Achievement motivation and innovation; determine the effectiveness of PBL model in improving students for junior hight school Bogor city achievement motivation and innovation. This research is based on the development research by Borg and Gall with three research and development stages, preliminary study, model development, and model test. The data analysis used during the development research were descriptive analysis, model validation analysis, and model effectiveness analysis with t-test independent samples. The results of the research concluded that: the achievement motivation and innovation of students for junior high school Bogor City is currently low and needs to be improved; the developed model is declared "fit foruse" by learning experts with more notes. The PBL model is declared effective in increasing the achievement motivation and innovation Islamic religious education students for junior high schoolin Bogor City. Abstrak Penelitian ini bertujuan mengetahui motivasi berprestasi dan inovasi siswa pada pendidikan agama Islam di SMP Kota Bogor; mengembangkan model Problem Based Learning (PBL) untuk meningkatkan motivasi berprestasi dan inovasi siswa pada pendidikan agama Islam di SMP Kota Bogor; mengetahui keefektifan model PBL dalam meningkatkan motivasi berprestasi dan inovasi siswa pada pendidikan agama Islam di SMP Kota Bogor. Penelitian ini merupakan penelitian pengembangan dari Borg and Gall terdiri dari tiga tahap, studi pendahuluan, pengembangan model, dan uji model. Analisis data yang digunakan meliputi analisis deskriptif, analisis validasi model, dan analisis keefektifan model dengan independen sampel-tes. Berdasarkan hasil penelitian disimpulkan bahwa: motivasi berprestasi dan inovasi siswa SMP Kota Bogor saat ini rendah dan perlu untuk ditingkatkan; model yang dikembangkan dinyatakan layak untuk digunakan model PBL dinyatakan efektif dalam meningkatkan motivasi berprestasi dan inovasi siswa pada pendidikan agama Islam di SMP Kota Bogor